A Psychology of Human Strengths: Fundamental Questions and Future Directions for a Positive Psychology. 2003
DOI: 10.1037/10566-015
|View full text |Cite
|
Sign up to set email alerts
|

Turning adversity to advantage: On the virtues of the coactivation of positive and negative emotions.

Abstract: Psychological stress has been known to have negative effects on health since the work of Cannon (1929) and Selye (1956). Contemporary research suggests that negative emotional reactions to stressors can also be detrimental to health, but that emotion management can foster healthy coping (Lazarus & Folkman, 1984). Those who ignore the occasional aggressive driver on the morning commute, for example, avoid the negative COACTIVATION OF POSITIVE AND NEGATIVE EMOTIONS 213

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
175
1
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 172 publications
(203 citation statements)
references
References 52 publications
21
175
1
2
Order By: Relevance
“…However, there is growing evidence suggesting that mixed feelings, or coactivation, is not only possible but quite common (Larsen et al 2003;Larsen, McGraw, and Cacioppo 2001;Schimmack 2001;Watson, Clark, and Tellegen 1988;Williams and Aaker 2002). We argue that explanations for counterhedonistic behavior should be consistent with newer evidence that people can simultaneously experience conflicting emotions, though that is presently not the case.…”
Section: Hedonism and Negative Affectmentioning
confidence: 82%
“…However, there is growing evidence suggesting that mixed feelings, or coactivation, is not only possible but quite common (Larsen et al 2003;Larsen, McGraw, and Cacioppo 2001;Schimmack 2001;Watson, Clark, and Tellegen 1988;Williams and Aaker 2002). We argue that explanations for counterhedonistic behavior should be consistent with newer evidence that people can simultaneously experience conflicting emotions, though that is presently not the case.…”
Section: Hedonism and Negative Affectmentioning
confidence: 82%
“…It has been proposed that dopaminergic activity at the level of the ACC is essential in the willingness to exert effort and to overcome response costs 1 (Walton et al, 2005). Similarly, Larsen et al (2003); also Folkman and Moskowitz, (2000) suggest that stressors should co-activate positive affect (dopaminergic) approach/appetition systems to overcome simultaneous activation of negative affect (cholinergic) avoidance/aversion systems to enable active, problem-focused coping. The level of activation of this dopaminergic mechanism of effort-allocation and engagement may be reflected in the amplitude of the ERN (Boksem et al, 2006a,b;Lorist et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have found that individuals experiencing positive mood and optimists do attend to negative, especially threatening, information when it is self-relevant and may hold a future advantage for them (Aspinwall & Brunhart, 1996;Estrada et al, 1997;Reed & Aspinwall, 1998;Larsen et al, 2003). Instead of individuals in positive moods merely viewing positive stimuli to maintain their moods, these individuals may instead actively seek out the most adaptive strategy in their information processing for future gains, even at the cost of short-term pleasure.…”
Section: Mood Maintenance and Broadeningmentioning
confidence: 99%
“…Optimists' attentional bias away from negative stimuli, however, may be dependent on the self-relevance of the stimuli. Optimism as well as other positive mood states may help facilitate the processing of negative information and experiences (Larsen, Hemenover, Norris, & Cacioppo, 2003). In one study, self-affirming their kindness before being shown threatening stimuli caused individuals to be more open and less biased in their processing of the stimuli as well as to more quickly orient toward the selfrelevant but threatening health-risk information (Reed & Aspinwall, 1998).…”
mentioning
confidence: 99%